-1+(n/2)=-4

Simple and best practice solution for -1+(n/2)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1+(n/2)=-4 equation:



-1+(n/2)=-4
We move all terms to the left:
-1+(n/2)-(-4)=0
We add all the numbers together, and all the variables
(+n/2)-1-(-4)=0
We add all the numbers together, and all the variables
(+n/2)+3=0
We get rid of parentheses
n/2+3=0
We multiply all the terms by the denominator
n+3*2=0
We add all the numbers together, and all the variables
n+6=0
We move all terms containing n to the left, all other terms to the right
n=-6

See similar equations:

| 1.5n+4=-26 | | 8=y/6-4 | | 17=2m+3 | | 12-7t=-4t | | -1(n/2)=-4 | | 7h-5=-4+9+8h | | 6a-6=-9+13a | | z/4-16=17 | | 3w-10=10-7w | | -11(3+3z)=3(-15z-6) | | 2y=-1-8 | | h/2+17=23 | | 5+5-6r=4-8r | | x+3(5-x)=17 | | 5(2x+1)+7(4x+2)=6 | | -13+-5s=-63 | | 6c-9=3c+9 | | -2+(v/2)=-6 | | -5y=7-4y | | -5y+6y-81=7y+102× | | k/7+-23=-16 | | –13t+19t−–18=–12 | | 7-4x-8=19 | | –10h−–8h=8 | | 10-6f=-10-10f | | 2r+5(-6-8r)=5r-4r | | -1=7b-5-8b | | P=5m^2+12m+2 | | -9x+8=-8x+6 | | 4(5x−3)=3(2x+1) | | (c/4)+5=6 | | 20+(y-10)= |

Equations solver categories